2007
DOI: 10.1038/sj.eye.6702906
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour efficacy of the brimonidine/timolol fixed combination versus therapy with the unfixed components

Abstract: Purpose To evaluate the 24-h intraocular pressure (IOP) control of brimonidine/timolol fixed combination (BTFC) versus the unfixed combination of its individual components, each dosed twice daily, in patients with primary open-angle glaucoma or ocular hypertension. Methods An observer-masked, randomized, crossover, active-controlled, two-centre comparison. Following a 6-week medicine-free period, patients were randomized to BTFC or to the unfixed combination of brimonidine and timolol for 3 months. Patients th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
2
13
0
1
Order By: Relevance
“…Nevertheless, the mean IOP reduction over 24 h (22%) observed with BTFC was less than anticipated. 17 Although this range of pressure reduction is consistent with the evidence obtained from the regulatory trials for BTFC, 18,19 the extent of the 24-h IOP reduction is less than that observed with DTFC. 20 Specifically, with DTFC, reported daytime IOP reduction ranges from 27 to 33% [21][22][23][24] and the 24-h IOP reduction ranges between 26 and 28% [25][26][27] in published studies.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, the mean IOP reduction over 24 h (22%) observed with BTFC was less than anticipated. 17 Although this range of pressure reduction is consistent with the evidence obtained from the regulatory trials for BTFC, 18,19 the extent of the 24-h IOP reduction is less than that observed with DTFC. 20 Specifically, with DTFC, reported daytime IOP reduction ranges from 27 to 33% [21][22][23][24] and the 24-h IOP reduction ranges between 26 and 28% [25][26][27] in published studies.…”
Section: Introductionsupporting
confidence: 76%
“…The results herein may explain for the first time why the 24-h IOP reduction provided by BTFC may be less than might be anticipated. Considering the previously documented 24-h efficacy of brimonidine and BTFC, 17,33,35 it is conceivable that the reason for the reduced efficacy with BTFC may be the shorter duration of action of brimonidine, when instilled twice daily, whereas dorzolamide may have a longer duration of action and better night-time efficacy. 20,37 We observed the mean IOP, when six time-points over 24-h are averaged, to be significantly better with DTFC than with BTFC.…”
mentioning
confidence: 99%
“…The number of patients reported to discontinue from the study due to intolerance or adverse events was found to be higher in the fixed combination groups in five versus two studies (table 5). However, the number of patients involved was extremely small in relation to the study population sizes (1–6%) with the exception of Konstas et al 13 (12.5%).…”
Section: Resultsmentioning
confidence: 87%
“…They incorporated four of the five glaucoma fixed combinations on the current market: Cosopt ,12 15 Combigan ,10 13 Duotrav 11 14 and Xalacom 9. The only study for Ganfort 20 was excluded due to its short duration.…”
Section: Resultsmentioning
confidence: 99%
“…FCBT and FCDT are more efficacious than either of both their components administered as monotherapy 30,31 and equally efficacious compared with concomitant administration of their active components. 32,33 We demonstrated that after 4 and 12 weeks of treatment, both FCDT and FCBT led to significant reductions in mean IOP from their corresponding postinjection IOP values (Table 3). However, FCBT was associated with significantly greater reductions in mean IOP at both the 4th-and 12th-week visits compared with FCDT (Table 4).…”
Section: Discussionmentioning
confidence: 82%